The Rise of TikTok during the Pandemic: Association between TikTok Consumption and Students’ Engagement - Salasac, Clarissa; Lobo, Joseph (Lamintang Education and Training Centre, in collaboration with the International Association of Educators, Scientists, Technologists, and Engineers (IA-ESTE), 2022)
TikTok has been one of the most used Social Networking Services (SNS) worldwide. It has grown into a platform with a broad range of content, including sports, fashion, performing arts, and education, encouraging learners to join the community. In this, this descriptive-correlational aimed to determine the relationship between TikTok Utilization and the Level of Engagement of BPeA students of the City College of Angeles. After gathering data from 103 respondents through an online survey, the findings revealed that the BPeA students undergoing online classes use the TikTok application moderately and responsibly. Also, the level of students' engagement during online classes was found to be very high. Furthermore, a significant positive relationship was observed between TikTok utilization and students' engagement. Based on the findings, the researchers recommend that the Institute of Education, Arts, and Sciences (IEAS), in partnership with the College Guidance Office (CGO), collaborate on providing webinars or trainings on how SNS such as TikTok can be a helpful tool or distraction at the level of engagement of the students. Additionally, instructors/professors may also use the TikTok application as an educational tool to provide a better and more engaging classroom environment. Moreover, conducting the same study with the addition of other degree programs offered by the college to determine if the results may support or refute the findings is highly recommended. Lastly, other variables may be added to this present study to understand further the relationship between TikTok consumption and students' engagement.